2013
DOI: 10.1145/2499370.2462174
|View full text |Cite
|
Sign up to set email alerts
|

Transit

Abstract: With the maturing of technology for model checking and constraint solving, there is an emerging opportunity to develop programming tools that can transform the way systems are specified. In this paper, we propose a new way to program distributed protocols using concolic snippets. Concolic snippets are sample execution fragments that contain both concrete and symbolic values. The proposed approach allows the programmer to describe the desired system partially using the traditional model of communicating extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Results showed that SCYTHE quickly and precisely solved more than 74% of the benchmarks and 80% out of these solved benchmarks were solved within a few seconds. Our algorithm solved 51 more cases within 600 seconds compared to the enumerative search algorithm [25,37] and outperformed SQLSynthesizer [40] on their project benchmarks with 4 more cases solved.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Results showed that SCYTHE quickly and precisely solved more than 74% of the benchmarks and 80% out of these solved benchmarks were solved within a few seconds. Our algorithm solved 51 more cases within 600 seconds compared to the enumerative search algorithm [25,37] and outperformed SQLSynthesizer [40] on their project benchmarks with 4 more cases solved.…”
Section: Introductionmentioning
confidence: 94%
“…Such algorithms enumerate all programs in the program space of a given depth limit and retain only those consistent with the provided I/O examples. Previous enumerative synthesizers [2,25,37] adopt the concept of equivalence classes to optimize the search process: they group programs into equivalence classes based on their behaviors on the input example to compress the search space. The search then proceeds iteratively: within each stage, the algorithms enumerate all programs in the current search space, group them based on an equivalence metric, and proceed to the next stage.…”
Section: Enumerative Search With Equivalence-classmentioning
confidence: 99%
“…A user specifies the behaviour of the desired program by a number of input-output examples [19]. Singh and Gulwani transformed strings and data types in spreadsheets [17,28] and Udupa et al were able to synthesize protocols from a given skeleton and examples [32].…”
Section: Smtmentioning
confidence: 99%
“…The main difference is the way of specification. Like in many traditional synthesis approaches [16,17,28,32], targets in [27] are specified by using properties of executed programs. More specifically, relations on inputs and outputs are defined.…”
Section: Smtmentioning
confidence: 99%
See 1 more Smart Citation